Bioethanol from hydrolysate of ultrasonic processed robust microalgal biomass cultivated in dairy wastewater under optimal strategy. (1st April 2022) - Dhandayuthapani, K.; Kumar, P. Senthil; Chia, Wen Yi; Chew, Kit Wayne; Karthik, V.; Selvarangaraj, H.; Selvakumar, P.; Sivashanmugam, P.; Show, Pau Loke
Abstract: Microalgal biomass produced from the inexpensive nutrient medium is a potential raw source for manufacturing different essential products covering a broad spectrum of applications. In this study, six separate microalgal strains were isolated from lake freshwater and screened based on their growth and biomass productivity in 10% raw dairy wastewater (DWW). Statistically optimized growth parameters of microalga using CCD-RSM were light intensity 65 μE m −2 s −1, pH 7, temperature 35 °C and agitation 150 rpm with maximum dry biomass yield 16.35 ± 0.34 g/L in ultrasonic pre-treated DWW (UPDWW) (75%, v/v). The physicochemical properties of 75% UPDWW were observed pre- and post-algal cultivation and found 94.8% COD removal, indicating the strain's potential phycoremediation. At optimal conditions, hydrolysate of C. sorokiniana NITTS3 biomass yielded 13.67 g/L of bioethanol using selected yeast. The findings of this investigation suggest that C. sorokiniana NITTS3 isolated from freshwater could effectively be used for phycoremediation of DWW with concomitant biomass production as an appropriate feedstock for bioethanol production. Highlights: Robust microalga was isolated from freshwater and screened for biomass production. Microalga yielded 16.35 ± 0.34 g/L biomass in ultrasonic treated dairy wastewater. Phycoremediation of dairy industry wastewater achieved 94.8% COD removal. Hydrolysate of ultrasonic digested microalgal biomass yielded 13.67 g/L of ethanol.